Narrative transportation in global brand content - Romppanen, Iiro (My University, 2016)
People understand life and events around them through narratives. Narratives are a new way for marketers to convey messages to consumers about their brands and products. Brand narratives are an effective way to reach out to people due to their influential nature. Narratives have a power to change beliefs and attitudes, making them relevant and interesting for any marketer. The power of narratives has to do with narrative transportation, which narratives can trigger in people. A transported person is more likely to perceive brand or product in a more positive light. The creators of the narrative are able to influence the content of the narrative through message factors that work as antecedents for narrative transportation. This study explored narrative transportation qualities of well established advertisements. The study uses qualitative content analysis to analyze and identify narrative transportation antecedents among Cannes Lion grand prix winners in the film category between years 2005 to 2015 (15 in total). The narrative transportation antecedents are identifiable characters, imaginable plot and verisimilitude, which were used in the analysis of the data. The study analyzes the winners to make judgment on whether they can trigger narrative transportation or not. It was found that the Cannes Lion grand prix winner advertisement mostly had identifiable narratives in them. In most of the advertisement (ten out of fifteen) at least two out of three antecedents were found, thus most of them are able to trigger narrative transportation. The study also found that most narratives in the advertisement were able to be linked to the main brand narrative of the advertiser. In four of the advertisements the link to the brand narrative was not able to be established. The study concludes by discussing certain factors and aspects of the advertisements that were identified to further enhance the narrative transportation qualities of the advertisement.

Ihmiset ymmärtävät elämää ja tapahtumia ympärillään narratiivien kautta. Narratiivit ovat tehokas keino markkinoijille välittää viestejä kuluttajille brändistään ja tuotteestaan. Brändi narratiivit ovat tehokas keino saavuttaa ihmisiä, koska niillä on voima vaikuttaa. Narratiiveilla on voima vaikuttaa ihmisten uskomuksiin ja asenteisiin, mikä tekee narratiiveista merkityksellisiä markkinoijille. Narratiivien voima perustuu narratiiviseen transportaation. Kun ihminen transportoituu narratiivin johdosta, on todennäköistä että hän kokee brändin tai tuotteen positiivisesti. Narratiivien luojalla on mahdollisuus vaikuttaa sen sisältöön siten, että se johtaa parempaan narratiiviseen transportaatioon. Tämä tutkimus tutkii narratiivista transportaatiota ja siihen johtavia tekijöitä Cannes Lions grand prix –palkinnon voittaneissa mainoksissa vuosien 2005 ja 2015 välillä (15 mainosta yhteensä). Tutkimus pyrkii etsimään tutkimusaineistosta narratiiviseen transportaatioon johtavia tekijöitä, jotka ovat itse narratiivin sisällöstä kiinni. Nämä tekijät ovat tunnistettavat hahmot, kuviteltava juoni ja verisimiliteetti. Tutkimus pyrkii toteamaan näiden tekijöiden avulla sen, onnistuuko mainos luomaan narratiivista transportaatiota. Tutkimus tunnisti suurimassa osassa Cannes Lion grand prix –voittajia narratiivin, ja useimmissa se oli yhdistettävissä mainostajan brändin pää narratiiviin. Useimmat voittajat sisälsivät ainakin kaksi kolmesta narratiiviseen transportaatioon johtavaa tekijää, mikä kertoo sen että nämä mainokset onnistuivat luomaan narratiivista transportaatiota. Useimmat mainokset sisälsivät narratiivin, joka oli linkitettävissä mainostajan brändin narrativiin, mutta neljässä mainoksessa tätä linkkiä ei voitu luoda. Tämä tutkimuksen johtopäätökset keskustelevat tutkimuksessa löydettyjen tekijöiden roolia narratiivisen transportaation luomisessa.